2020
DOI: 10.1016/j.dld.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and intestinal inflammation: Role of fecal calprotectin

Abstract: COVID-19 and intestinal inflammation: Role of fecal calprotectin ✩Dear Editor , ✩ The members of the GEMELLI AGAINST COVID-19 group can be found in the Appendix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 9 publications
4
57
0
Order By: Relevance
“…Among the eight included quantitative studies, five studies discussed the comparison of serum levels of calprotectin in severe and non-severe COVID-19 patients [12,14,[25][26][27] ( Table 3). Three of the studies reported a comparison of the fecal calprotectin [18,28,29] ( Table 3). The two included qualitative studies conducted an RNA-sequence analysis of a single cell [33,34] with reports documenting more elevated levels of calprotectin expression in severe compared to non-severe COVID-19 (Table 4).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the eight included quantitative studies, five studies discussed the comparison of serum levels of calprotectin in severe and non-severe COVID-19 patients [12,14,[25][26][27] ( Table 3). Three of the studies reported a comparison of the fecal calprotectin [18,28,29] ( Table 3). The two included qualitative studies conducted an RNA-sequence analysis of a single cell [33,34] with reports documenting more elevated levels of calprotectin expression in severe compared to non-severe COVID-19 (Table 4).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The mean serum/fecal calprotectin was compared between the severe and non-severe groups of COVID-19 infection in these included studies (Figure 2). Among the included studies, all of the serum quantitative studies were considered to be of good quality [12,14,[25][26][27] while two of the fecal studies were of good quality [28,29] except Effenberger et al [18], which was considered to be of moderate quality (Table 2). Further, the two included studies in the qualitative category had good (Unterman et al) [33] and low (Livanos et al) [34] quality respectively (Table 4).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, patients with COVID-19-associated thrombosis had significantly higher blood levels of NETs and neutrophil activation markers such as CLP compared with COVID-19 patients without thrombosis [ 85 ]. Additionally, many studies support that fecal CLP indicates intestinal inflammation in COVID-19 [ 86 , 87 , 88 ].…”
Section: Clp In Respiratory Infectionsmentioning
confidence: 99%